Determinants of priority for lifelong learning: A study of Universiti Utara Malaysia City Campus students - Hwang, Kee Suan; Thi, Lip Sam (?, 2010)
The objectives of the study were to examine students’ perceived priority for lifelong learning; and to investigate the factor(s) that influence their priority for lifelong learning. The sample comprised of 234 students from UUM City Campus, who are currently pursuing their studies on a part-time basis. A model was developed to examine the relationships between the factors that are perceived to be associated with lifelong learning participation. Factor analysis and reliability test were carried out on items adapted from Education Participation Scale (EPS) by Boshier and Collins (1983). Five factors were identified that were perceived to influence students’ priority for lifelong learning namely,social contact, professional advancement, cognitive interest, external expectation and emotional relief. Regression analysis was performed to examine the relationship between the dependent and independent variables. The results showed that priority for lifelong learning was only associated with adult learners’ cognitive interest while other factors were not significantly associated with their priority for lifelong learning.